2020
DOI: 10.1093/cz/zoaa024
|View full text |Cite
|
Sign up to set email alerts
|

The group size effect and synchronization of vigilance in the Tibetan wild ass

Abstract: Vigilance behavior is considered as an effective strategy for prey species to detect predators. An individual benefits from living in a group by reducing the time spent being vigilant without affecting the probability of detecting a predator. However, the mechanism producing a decrease in vigilance with increasing group size is unclear. Many models of vigilance assume that group members scan independently of one another. Yet in recent studies, the other two patterns of vigilance, coordination and synchronizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 47 publications
0
8
1
Order By: Relevance
“…Some of our results were not as expected. Other studies have reported some persistent synchronization of vigilance, but the difference in proportions has often been small (Pays et al 2007a(Pays et al , b, 2012Öst and Tierala 2011;Podgórski et al 2016;Wang et al 2020), while in our study the difference was large. This larger difference in proportions may be explained by a group size effect on synchronization (Beauchamp 2015).…”
contrasting
confidence: 74%
See 3 more Smart Citations
“…Some of our results were not as expected. Other studies have reported some persistent synchronization of vigilance, but the difference in proportions has often been small (Pays et al 2007a(Pays et al , b, 2012Öst and Tierala 2011;Podgórski et al 2016;Wang et al 2020), while in our study the difference was large. This larger difference in proportions may be explained by a group size effect on synchronization (Beauchamp 2015).…”
contrasting
confidence: 74%
“…We found that perch behavior resulted in less time foraging, however this reduction did not result in lower body condition or lower survival chances. When testing the assumption of taking turns, the results may show that coordination of vigilance is absent altogether (Hing et al 2019), synchronized (e.g., our study; Wang et al 2020), or switches between synchronization and taking turns dependent on level of disturbance and predation risk (Kong et al 2021). In Barbary ground squirrels, perch behavior was synchronized because the observed time that at least one individual is perched was smaller than the expected time, resulting in a difference in proportions smaller than zero.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…The effect of group information sharing on cognitive demands is wellillustrated by vigilance behaviors. Individual vigilance behavior performance rates decrease in the presence of conspecifics in some species (McBlain et al, 2020;Wang et al, 2021), and predator detection can be faster and more accurate in social groups compared to lone individuals (Ward et al, 2011). However, the need for increased ability to produce, detect and respond to social signals can involve additional cognitive and neural costs.…”
Section: Attributes Of Social Behavior: Information Sharingmentioning
confidence: 99%